The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.jasms.2010.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Separation and identification of structural isomers by quadrupole collision-induced dissociation-hydrogen/deuterium exchange-infrared multiphoton dissociation (QCID-HDX-IRMPD)

Abstract: A new approach that uses a hybrid Q-FTICR instrument and combines quadrupole collisioninduced dissociation, hydrogen-deuterium exchange, and infrared multiphoton dissociation (QCID-HDX-IRMPD) has been shown to effectively separate and differentiate isomeric fragment ion structures present at the same m/z. This method was used to study protonated YAGFL-OH (free acid), YAGFL-NH 2 (amide), cyclic YAGFL, and YAGFL-OCH 3 (methyl ester). QCID-HDX of m/z 552.28 (C 29 T andem mass spectrometry is widely used for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…Different tools, sometimes in combination, have been applied for obtaining information on the structures of peptide fragment ions, including theoretical calculations [9,10], multi-stage mass spectrometry (MS/MS, or MS n ) [3,4,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], ion mobility spectrometry (IMS) [29,30], hydrogen-deuterium exchange (HDX) [22,31,32], and infrared multiple photon dissociation (IRMPD) spectroscopy [5,22,[31][32][33][34][35][36][37][38][39][40][41][42]. While spectroscopy is a particularly powerful way to obtain detailed information about the structures of gas phase molecules, approaches based on IRMPD feature certain drawbacks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different tools, sometimes in combination, have been applied for obtaining information on the structures of peptide fragment ions, including theoretical calculations [9,10], multi-stage mass spectrometry (MS/MS, or MS n ) [3,4,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], ion mobility spectrometry (IMS) [29,30], hydrogen-deuterium exchange (HDX) [22,31,32], and infrared multiple photon dissociation (IRMPD) spectroscopy [5,22,[31][32][33][34][35][36][37][38][39][40][41][42]. While spectroscopy is a particularly powerful way to obtain detailed information about the structures of gas phase molecules, approaches based on IRMPD feature certain drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing complexity of the fragment ion structures, support from other sources of information becomes necessary for unraveling complicated IRMPD spectra. This can be achieved by combining spectroscopy with other techniques [22,31,32] or by comparison of the spectra with chemically modified species in which cyclization is either induced or inhibited [36,38,39,42,44].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the attention concerning peptide fragments has been devoted to b n ions [12,[17][18][19][20][21][22][23][24][25]. Nonetheless, a n CID fragments [26][27][28] as well as c n fragment ions [29] generated via electron capture dissociation have also been investigated by IR spectroscopy.…”
mentioning
confidence: 99%
“…In a complementary IRMPD spectroscopy and HDX study on oligoglycine b fragments, Chen et al demonstrated a size effect on the propensity to form macrocycle structures: the smaller b 2 and b 3 exclusively adopt oxazolone structures, whereas mid-sized fragments (b 4 -b 7 ) exhibit a mixture of oxazolone and macrocycle structures; for the largest b fragment, b 8 , only macrocycle structures were confirmed [18]. Similar trends were observed for b 2 -b 4 for Leuenkephalin [21], as well as b 5 from YAGFL-NH 2 [22]. Computational results by Bleiholder et al confirmed that for permuted b 5 fragment ions, the macrocycle structures were energetically favored over the linear oxazolones [30].…”
Section: Introductionmentioning
confidence: 77%
“…"Fast-" and "slow"-exchanging b fragment structures have been distinguished in this way by a number of groups [18][19][20][21][22][23]. Quantification of "fast" versus "slow" structures can be performed by an analysis of the kinetic rates.…”
Section: Introductionmentioning
confidence: 99%